KEHARAMAN PERNIKAHAN SEDARAH (INCEST) DITINJAU DARI HUKUM ISLAM: Vol 06 Nomer 02 September 2019 - Aziz, Abdul; Rahim, Mif; Chamim, M (Irtifaq, 2019)
This article discusses the prohibition of incest in terms of Islamic law. With a literature study, researchers explore various aspects related to incest in terms of the influence of blood marriage on bloodline descent and blood marriage according to Islamic law. The author examines library resources to answer the problem. With descriptive methods, data analysis by reviewing and linking the data obtained in order to get clarity on the problems discussed both deductively and inductively. Results from this study: one, marriages performed between families tend to produce abnormal offspring more often than non-family marriages. A person who has blood relations will be more likely to give the same genes compared to people who are not related by blood, second, in the meantime, marriage between close relatives can weaken the offspring and marry them is clearly prohibited. But illat (reason) is not clearly stated in the text. Illat (reason) is only obtained from istinbath, ijtihad / mind, or mere estimation. Every thing that is forbidden by Allah there must be wisdom and benefits Keywords: Forbidden, Blood Marriage, Islamic Law